2016
DOI: 10.1007/s10509-016-2730-3
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the late B-type stars HD 67044 and HD 42035

Abstract: While monitoring a sample of apparently slowly rotating superficially normal bright late B and early A stars in the northern hemisphere, we have discovered that HD 67044 and HD 42035, hitherto classified as normal late B-type stars, are actually respectively a new chemically peculiar star and a new spectroscopic binary containing a very slow rotator HD 42035 S with ultra-sharp lines (vsini = 3.7 km/s) and a fast rotator HD 42035 B with broad lines. The lines of Ti, Cr, Mn, Sr, Y, Zr and Ba are conspicuous feat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…4), it can be seen that the binary consists of a very slowly rotating component and a very rapidly rotating component. This is consistent with the findings of Monier et al (2016), who report numerous peculiarities of the chemical abundances, which we also observe in our spectra. We find a T eff of 10500 K which is consistent with the values given in Monier et al (2016).…”
Section: Hd 42035supporting
confidence: 94%
See 2 more Smart Citations
“…4), it can be seen that the binary consists of a very slowly rotating component and a very rapidly rotating component. This is consistent with the findings of Monier et al (2016), who report numerous peculiarities of the chemical abundances, which we also observe in our spectra. We find a T eff of 10500 K which is consistent with the values given in Monier et al (2016).…”
Section: Hd 42035supporting
confidence: 94%
“…This is consistent with the findings of Monier et al (2016), who report numerous peculiarities of the chemical abundances, which we also observe in our spectra. We find a T eff of 10500 K which is consistent with the values given in Monier et al (2016). However, as stated by Monier et al (2016), this value has significant flux contributions from both stars, and so the evolutionary status of both stars remains unclear.…”
Section: Hd 42035supporting
confidence: 94%
See 1 more Smart Citation
“…We have already reported on the discovery of 4 new HgMn stars (Monier et al 2015) whose spectra display strong Hg II lines at 3984 Å and strong Mn II lines. In the process of our analysis of the B8-B9V sample, we also found that HD 67044 is most likely another new HgMn star (Monier et al 2016). Royer et al (2014) performed abundance analyses for C, O, Mg, Si, Ca, Sc, Ti, Cr, Fe, Sr, Y, Zr using Takeda's automated procedure and classified HR 8844 as "probably normal": the four criteria used for the automatic classification were not fully consistent, depending on the chemical species used.…”
Section: Introductionmentioning
confidence: 81%
“…The derived abundance pattern of HD 87240 departs strongly from the solar composition which definitely shows that HD 87240 is not a superficially normal late B star but is definitely a new CP star. We have already reported on the discovery of 6 new CP stars of the HgMn type among late B-type stars in Monier et al (2015), Monier et al (2016) and Monier et al (2018). HD 87240 has overabundances of both the rare earths and of Pt and Hg and its effective temperature and surface gravity place it among the Bp Si and the HgMn stars.…”
Section: Discussionmentioning
confidence: 99%